Access to education in Europe : a framework and agenda for system change - Downes, Paul [Verfasser] (Springer Science + Business Media, 2014)
"This book identifies key elements of an international framework to develop systems-level change to promote access to education, including higher education, for socio-economically marginalized groups. It is based on interviews with senior government officials and senior management in universities, non formal education and prisons across 12 countries in Europe. The book identifies systemic obstacles to and opportunities for promotion of access to education for socio-economically excluded groups that are issues transferable to other countries' contexts. It adopts a systemic focus on access across a range of domains of education, both formal higher education and non-formal education, as well as prison education. Through a focus on a more dynamic structuralist systems framework it develops an innovative post-Bronfenbrennerian view of system levels in lifespan developmental and educational psychology. (...)" (Verlag, BIBB-Doku)
Keywords: S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; T 4.5 Soziologie; I 2.2 Europa; Bildungschance; Soziale Ungleichheit; Benachteiligter; Durchlässigkeit im Bildungssystem; Hochschulzugang; Bildungssoziologie; EU-Bildungspolitik; Europa